1989 Whitechapel Open : East End Open Studios. - Lampert, Catherine (London : Whitechapel Art Gallery, 1989)
Aaron, Cheryl ; Al-ani, Jananne ; Alien, tim ; Arif, Saleem ; Bennett, Geoffrey ; Bermejo, Laetitia ; Bhimji, Zarina ; Blackett, Vivien ; Blacklock, George ; Bowling, Frank ; Buck, Louisa ; etc.
1989 Whitechapel Open - East End Open Studios, Whitechapel Art Gallery, London, 15 September - 29 October 1989
boek